Understanding Drug Release Data through Thermodynamic Analysis - Liberato Cavalcanti Freire, Marjorie Caroline; Alexandrino, Francisco; Marcelino, Henrique Rodrigues; Souza Picciani, Paulo Henrique de; Holanda e Silva, Kattya Gyselle de; Genre, Julieta; Oliveira, Anselmo Gomes de [UNESP]; Tabosa do Egito, Eryvaldo Socrates (Mdpi Ag, 2017)
Understanding the factors that can modify the drug release profile of a drug from a Drug-Delivery-System (DDS) is a mandatory step to determine the effectiveness of new therapies. The aim of this study was to assess the Amphotericin-B (AmB) kinetic release profiles from polymeric systems with different compositions and geometries and to correlate these profiles with the thermodynamic parameters through mathematical modeling. Film casting and electrospinning techniques were used to compare behavior of films and fibers, respectively. Release profiles from the DDSs were performed, and the mathematical modeling of the data was carried out. Activation energy, enthalpy, entropy and Gibbs free energy of the drug release process were determined. AmB release profiles showed that the relationship to overcome the enthalpic barrier was PVA-fiber > PVA-film > PLA-fiber > PLA-film. Drug release kinetics from the fibers and the films were better fitted on the Peppas-Sahlin and Higuchi models, respectively. The thermodynamic parameters corroborate these findings, revealing that the AmB release from the evaluated systems was an endothermic and non-spontaneous process. Thermodynamic parameters can be used to explain the drug kinetic release profiles. Such an approach is of utmost importance for DDS containing insoluble compounds, such as AmB, which is associated with an erratic bioavailability.
Keywords: Amphotericin B; drug release; kinetic profile; thermodynamics; hydrogels; films; nanofibers